(untitled) (Bangladesh Medical Journal Khulna, 2022)
Background: Urinary bladder tumours are common lesions in man and woman. Mortality and morbidity depend on the grade and stage of tumour at the time of diagnosis. Early diagnosis is associated with good prognosis, but there are limited data in Bangladesh about such practice. Objective: The aim of the study is to see the histomorphological pattern of urinary bladder tumors in different age groups and to see the pattern of presentation of various urinary bladder tumours. Methodology: A total 150 cases, clinically, sonographically and/or cystoscopically suggestive of urinary bladder tumor were included in this study. Specimens were collected after surgical resection in a container containing 10% formalin. The specimens were processed by paraffin embedding method and stained by routine Haematoxylin and Eosin stain for microscopic examination. The results of this study were calculated by standard statistical formula. Results: This study focuses mostly on the histological examination of the specimen of urinary bladder mass with their clinical findings. The microscopic type of 150 cases of urinary bladder tumor was: 143 (95.33%) were papillary urothelial carcinoma, 4 (2.66%) were adenocarcinoma, 2 (1.33%) were squamous cell carcinoma and I (66%) was carcinosarcoma. The main clinical presentations were haematuria, irritative voiding of urine and flank pain. Conclusion: Papillary urothelial carcinoma stage T2 are much more common in Bangladesh. Regarding association with risk factor, smoking plays very important part for making bladder tumour. Bang Med J Khulna 2021; 54 : 03-07